RANCANG BANGUN SISTEM INFORMASI PENJUALAN BRIKET ARANG BERBASIS WEBSITE (SIJABRIK) - Lydia Salvina Helling; Sabira Nazahah Nada (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
In this modern era, of course, every good company has a company standard that greatly affects all operational and non-operational activities such as selling goods. PT Jomini Coco Internasional is a company that was established in 2013, PT Jomini Coco Internasional is a company engaged in charcoal briquettes. However, the current sales system at PT. Jomini coco Internasional still uses the conventional system because in the process of processing sales data and making reports still using computers in the form of standard applications, namely Microsoft Word and Microsoft Excel, recording customer documents still using record books and also stored in different computers so that it can cause problems. such as damage and loss of important documents. Therefore PT Jomini Coco Internasional requires a web-based information system that aims to manage data on sales of goods and can provide convenience for every user in accessing information on goods and managing data. The software development method used is using a prototype. This website-based Charcoal Briquette Sales Information System is expected to facilitate transactions and the preparation of useful reports for PT Jomini Coco Internasional.